Currency compositions of international reserves - recent developments - Falk Hendrik Laser; Alexander Mihailov; Jan Weidner (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2024)
This policy brief presents a new comprehensive dataset on the currency compositions of international reserves of 64 economies from 1996 to 2023. The dataset contains country-specific shares in international reserves for the eight major international currencies, i.e. the United States Dollar (USD), the Euro (EUR), the Japanese Yen (JPY), the British Pound (GBP), the Canadian Dollar (CAD), the Australian Dollar (AUD), the Chinese Yuan or Renminbi (CNY), and the Swiss Franc (CHF). The dataset provides an up-to-date and comprehensive account of publicly available data on the denomination of international reserves, including data on international currencies other than the USD, EUR, JPY, and GBP. While the USD and the EUR remain the dominant global reserve currencies, the data indicate their significance has diminished as countries diversify their reserves. Currencies, including the CNY, have gained prominence, hinting at a gradual fragmentation of the international monetary system. While the USD should retain its leading role in the medium term, ongoing geoeconomic shifts suggest a move towards a multipolar reserve currency landscape. The eventual look of this landscape will depend on the credibility of reserve currency candidates and their ability to retain the characteristics that make them desirable as reserve currencies in the face of future economic and political developments.
urn:nbn:fi-fe2024090669648
Keywords: 330; International reserves; currency composition; central banks; monetary system